Subsidiaritas Sebagai Prinsip Sosial Dalam Upaya Menyelamatkan Masyarakat Lokal Dari Ancaman Sawit - Korain, Yulianus (Jurnal Sosial Teknologi, 2025)
This research focuses on subsidiarity as a social principle in an effort to save local communities from the threat of oil palm, a phenomenological theological study, which explores the values contained in Catholic Church Documents as a foundation in examining the social situation experienced by local communities as customary landowners. In fact, this research is more directed at the social life of local communities as customary landowners, whose land is turned into oil palm plantations. This is what the Church calls subsidiarity. Subsidiarity actually means an attitude that Jesus started when fighting for the dignity of the marginalised, oppressed, poor and simple. The Church's struggle for local communities is a concrete manifestation of Jesus' attitude. Furthermore, the author analyses the subsidiarity of local communities by using qualitative methods (observations, interviews), data studies and Church documents. From the analysis, it was found that subsidiarity actually comes from Jesus, the proclaimer, fighter and liberator. This subsidiarity is what is being lived, internalised by the Church when fighting for the rights of local communities. All problems experienced by local communities, the government and the Church become easy and refreshing when returned to the main source of Jesus Christ, the liberator. Elements of subsidiarity are contained in Pope Francis' Encyclical on the Social Teaching of the Church during the Pandemic and the Encyclical Quadragesimo Anno (Encyclical of Pope Pius XI). These documents are very rich in spiritual values that guide the lives of government and Church leaders. Finally, this research will be contextualised in the problems of life and service of Church and government leaders in the diocese of Manokwari-Sorong.